High insulation and low temperature sintering MLCC ceramic material and preparation method thereof

By doping boron quantum doping and combining with modified copper oxide to form a composite structure with mesoporous silica, the MLCC ceramic material has solved the problems of low Curie temperature, low insulation resistance and poor life in high temperature environments, and achieved high insulation and low temperature sintering of the material and good accelerated life.

CN119751049AInactive Publication Date: 2025-04-04HANGZHOU XINGRONG TECH CO LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411926353.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-25
Publication Date
2025-04-04
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The Curie temperature of existing MLCC ceramic materials is low, the insulation resistance is small, and the acceleration life is poor in high temperature environments, which affects its actual use.

Method used

By doping the barium titanate with boron quantum dots and combining with the nitrogen quantum dots in the modified copper oxide, mesoporous silicon dioxide is introduced as a bridge to form a high-density composite structure, which improves the Curie temperature and insulation resistance of the material while ensuring a good acceleration life.

Benefits of technology

The Curie temperature and insulation resistance of MLCC ceramic materials are significantly improved, the accelerated life is extended, and the poor life of materials in the prior art under high temperature environments is solved.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The present invention belongs to the technical field of ceramic materials, and specifically relates to a high-insulation, low-temperature sintered MLCC ceramic material and a preparation method thereof. The present invention firstly dopes the main material barium titanate with boron quantum dots, which can be combined with nitrogen quantum dots in modified copper oxide during the subsequent sintering process, thereby forming a reinforcing phase in the ceramic material. At the same time, the introduced mesoporous silica can provide a place for the combination of boron quantum dots and nitrogen quantum dots, and can also be used as a carrier to load titanium dioxide nanoparticles in alumina composite materials and rare earth elements in yttrium-doped zirconium dioxide, using mesoporous silica as a bridge to form a high-density composite structure, which improves the Curie temperature and insulation resistance of the MLCC ceramic material through synergistic effects, while ensuring a good accelerated life.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of ceramic materials, and specifically relates to a high-insulation, low-temperature sintered MLCC ceramic material and a preparation method thereof. Background Art

[0002] Multi-Layer Ceramic Capacitor (MLCC) is a device made of insulating dielectrics and conductive electrodes arranged at intervals. It is widely used in oscillation, coupling, filtering and bypassing of various circuits. It is an important component of various consumer electronics, mobile terminals and household appliances. With the advent of the 5G era, MLCC will gradually develop towards high frequency, low power consumption, miniaturization and high energy storage density technology.

[0003] A Chinese patent (publication number CN114956808B) discloses an MLCC ceramic dielectric material and a preparation method thereof, a high temperature stable MLCC ceramic and a preparation method and application thereof, wherein BaTiO 3 As the main crystal phase of ceramics, it can provide higher dielectric constant and lower dielectric loss; dopant Al 2 O 3 Can promote the sintering activity of barium titanate ceramics, thereby reducing the sintering temperature; Bi 2 O 3 He Yi 2 O 3 It can be used as a frequency stabilizer to reduce the rate of change of dielectric constant with temperature at high temperature; CuO is used as a sintering aid; By using BaTiO 3 ·xAl 2 O 3 The components of the system can work together to make the MLCC ceramic dielectric material have better electrical performance stability at high temperatures after being sintered into ceramics. However, this patented technology does not solve the problems of low Curie temperature, low insulation resistance, and poor accelerated life in high temperature environments of MLCC ceramic materials sintered at low temperatures in the prior art, which seriously affects its actual use.

[0004] Therefore, how to modify the main components of MLCC ceramic materials and increase the Curie temperature of the materials through low-temperature sintering, increase the insulation resistance, and ensure a good accelerated life has become a direction that needs to be focused on. Summary of the invention

[0005] In view of the deficiencies in the prior art, the purpose of the present invention is to provide a high-insulation, low-temperature sintered MLCC ceramic material and a preparation method thereof, aiming to solve the problems of low Curie temperature, low insulation resistance, and poor accelerated life in high temperature environments of MLCC ceramic materials in the prior art.

[0006] The present invention firstly dopes the main material barium titanate with boron quantum dots, which can combine with the nitrogen quantum dots in the modified copper oxide during the subsequent sintering process, thereby forming a reinforcement phase in the ceramic material. At the same time, the introduced mesoporous silica can provide a place for the combination of boron quantum dots and nitrogen quantum dots, and can also be used as a carrier to load titanium dioxide nanoparticles in the alumina composite material and rare earth elements in yttrium-doped zirconium dioxide. The mesoporous silica is used as a bridge to form a high-density composite structure, which improves the Curie temperature and insulation resistance of the MLCC ceramic material through synergistic effect, while ensuring a good accelerated life.

[0007] The technical solution adopted by the present invention to solve the above technical problems is as follows:

[0008] The first aspect of the present invention provides a method for preparing a high-insulation, low-temperature sintered MLCC ceramic material, comprising the following steps:

[0009] Step S1: by weight, 6 to 8 parts of barium hydroxide octahydrate are added to 20 to 30 parts of deionized water, and stirred for 30 to 40 minutes, and then 6 to 10 parts of titanium dioxide and 14 to 16 parts of deionized water are added, and a hydrothermal reaction is carried out at 100 to 104° C. for 4 to 6 hours to obtain a hydrothermal product; the hydrothermal product is transferred to a ball mill, 10 to 12 parts of barium carbonate and 2 to 4 parts of boron quantum dots are added, and the ball milling is carried out for 20 to 24 hours, dried, and ground to obtain a powder, and the powder is placed in a muffle furnace for calcination to obtain boron quantum dot-doped barium titanate;

[0010] Step S2: In parts by weight, 80 to 90 parts of boron quantum dots doped with barium titanate, 4 to 6 parts of aluminum oxide, 3 to 5 parts of copper oxide, 1 to 3 parts of silicon dioxide, 1 to 3 parts of zirconium dioxide and 200 to 250 parts of deionized water are mixed and ball-milled for 6 to 8 hours to obtain a powder slurry, the powder slurry is spray-granulated and then pressed into a ceramic body, the ceramic body is subjected to low-temperature sintering treatment to obtain a high-insulation, low-temperature sintered MLCC ceramic material.

[0011] As a preferred technical solution of the present invention, the calcination treatment conditions include: a calcination temperature of 1000-1050° C., a heating rate of 4-6° C. / min, and a time of 100-120 min.

[0012] As a preferred technical solution of the present invention, the preparation method of the boron quantum dots comprises: adding 1 to 3 parts of boron powder to 60 to 80 parts of isopropanol by weight and mixing evenly, then adding 2 to 4 parts of boric acid and 6 to 8 parts of hydrogen peroxide, ultrasonically crushing at a power of 580 to 600 W for 2 to 4 hours, adding 2 to 4 parts of sodium borohydride after the ultrasonic crushing, stirring for 20 to 24 hours, centrifuging to obtain a supernatant, adding 1 to 3 parts of hydrazine hydrate to the supernatant, ultrasonically shaking for 10 to 20 minutes, and freeze-drying to obtain the boron quantum dots.

[0013] Boron quantum dots doped with barium titanate can change the lattice structure of barium titanate by introducing boron elements, and affect the mechanism of ferroelectric phase transition and increase the Curie temperature of the material by forming solid solutions or generating stress at grain boundaries. At the same time, the incorporation of boron quantum dots will affect the mobility of domain walls in barium titanate and increase the domain wall pinning effect, which can also lead to an increase in the Curie temperature.

[0014] As a preferred technical solution of the present invention, the aluminum oxide is an aluminum oxide composite material; the preparation method of the aluminum oxide composite material comprises: in parts by weight, 36 to 40 parts of aluminum oxide, 16 to 20 parts of titanium dioxide, 8 to 10 parts of methyltrioctylammonium chloride, 4 to 6 parts of 2-methyl-2,4-pentanediol and 2 to 4 parts of polyethylene glycol are uniformly mixed and dispersed by ball milling for 24 to 30 hours to obtain a mixed slurry; the mixed slurry is heat treated at 760 to 800° C. for 10 to 12 hours, and after cooling to room temperature, it is crushed and ground to obtain the aluminum oxide composite material.

[0015] As a preferred technical solution of the present invention, the particle size of the aluminum oxide is 100 to 300 nm.

[0016] Titanium dioxide nanoparticles can form a second phase in the alumina matrix, fill the tiny pores at the grain boundaries, reduce the conductive channels at the grain boundaries, and help reduce the conductivity of the grain boundaries, thereby improving the insulation resistance of the overall material; at the same time, titanium dioxide and alumina can form a heterogeneous structure, change the micromorphology and crystal orientation of the material, optimize the electric domain distribution, reduce local electric field concentration, and increase insulation resistance.

[0017] As a preferred technical solution of the present invention, the copper oxide is modified copper oxide; the preparation method of the modified copper oxide comprises: adding 2 to 4 parts of 2-azidoimidazole to 12 to 16 parts of tetrahydrofuran by weight and fully dissolving them, then adding 4 to 6 parts of polyethyleneimine, reacting at 60 to 70° C. for 20 to 24 hours; after the reaction is completed, adding 1 to 3 parts of deionized water, drying the tetrahydrofuran with a rotary evaporator, extracting with ethyl acetate, dialyzing the aqueous solution for 8 to 10 hours, filtering with a filter membrane, and cooling the filtrate. Freeze drying to obtain nitrogen quantum dots; in parts by weight, 30 to 40 parts of cupric acetate are added to 150 to 160 parts of deionized water and mixed evenly, then 2 to 4 parts of glacial acetic acid and 4 to 8 parts of nitrogen quantum dots are added and stirred for 40 to 60 minutes, the temperature is raised to 100 to 110° C. and stirred for reaction for 20 to 30 minutes, after the reaction is completed, 2 to 4 parts of a sodium hydroxide solution with a molar concentration of 1 mol / L are added, the mixture is cooled to room temperature, the precipitate is washed with deionized water and anhydrous ethanol in turn, and dried to obtain the modified copper oxide.

[0018] The nitrogen quantum dots of modified copper oxide can act as acceptor impurities to introduce additional electrons or holes into copper oxide, thereby reducing the number of free carriers and increasing the insulation resistance of the material. At the same time, the introduction of nitrogen quantum dots can adjust the band gap width of copper oxide, making it more difficult for electrons to jump from the valence band to the conduction band, thereby indirectly increasing the insulation resistance.

[0019] As a preferred technical solution of the present invention, the silica is mesoporous silica; the preparation method of the mesoporous silica comprises: in parts by weight, dissolving 20 to 30 parts of hexadecyltrimethylammonium chloride and 1 to 3 parts of triethanolamine in 200 to 240 parts of deionized water, heating and stirring to 90 to 96° C., then adding 20 to 30 parts of ethyl orthosilicate and 10 to 20 parts of bis-[3-(triethoxysilyl)propyl]-tetrasulfide, continuing stirring for 4 to 6 hours, centrifuging, and washing with water to obtain mesoporous silica.

[0020] Mesoporous silica can act as a thermal barrier, slowing down the speed of heat transfer from the outside to the inside, thereby protecting the internal structure from high temperature; at the same time, it can act as a flux to help optimize the sintering process, allowing the ceramic particles to be more closely combined together, thereby obtaining a denser and more uniform microstructure, which is beneficial to improving the accelerated life of MLCC ceramic materials.

[0021] As a preferred technical solution of the present invention, the zirconium dioxide is yttrium-doped zirconium dioxide; the preparation method of yttrium-doped zirconium dioxide comprises: in parts by weight, adding 10 to 12 parts of zirconium oxychloride, 8 to 10 parts of yttrium chloride and 4 to 6 parts of polyethylene glycol to 100 to 120 parts of deionized water and mixing them evenly, adding 16 to 20 parts of a 25% by mass sulfuric acid solution at 70 to 80° C. to obtain a mixed solution, heating the mixed solution to 140 to 150° C. for hydrothermal reaction for 6 to 8 hours, cooling to room temperature, adding ammonia water to adjust the pH to 7.4 to 7.8, centrifuging, washing, drying, and calcining to obtain yttrium-doped zirconium dioxide.

[0022] Pure zirconium dioxide will undergo multiple phase changes at different temperatures. Phase changes will cause volume changes, thereby inducing internal stress in the material. Yttrium-doped zirconium dioxide can inhibit phase changes, reduce volume changes caused by phase changes, and improve the thermal stability of the material, thereby obtaining a good accelerated life.

[0023] As a preferred technical solution of the present invention, the conditions for the low-temperature sintering treatment include: first heating to 1000-1100°C at a rate of 6-8°C / min and keeping warm for 30-40 minutes, then cooling to 860-900°C at a rate of 4-6°C / min and keeping warm for 6-8 hours.

[0024] The second aspect of the present invention provides a high-insulation, low-temperature sintered MLCC ceramic material prepared by the method described in the first aspect.

[0025] Compared with the prior art, the present invention has the following beneficial effects:

[0026] (1) During the low-temperature sintering process of the boron quantum dots doped with barium titanate and modified copper oxide of the present invention, nitrogen quantum dots can be used as donor impurities to fill the lattice defects around the boron quantum dots, thereby improving the electronic structure of the material through the interaction of quantum dots. At the same time, the boron quantum dots and nitrogen quantum dots penetrate each other and react to form boron nitride, which can play the role of a reinforcing phase in the ceramic material. The Curie temperature and insulation resistance of the MLCC ceramic material are improved through synergistic effects, while ensuring a good accelerated lifespan.

[0027] (2) The mesoporous silica of the present invention can be loaded with materials through the mesopores on its surface. As a carrier, it can load titanium dioxide nanoparticles in alumina composite materials, rare earth elements in yttrium-doped zirconium dioxide, and provide a place for the combination of boron quantum dots and nitrogen quantum dots. Using mesoporous silica as a bridge, a dense network structure is constructed, which effectively improves the Curie temperature, insulation resistance, accelerated life and other properties of MLCC ceramic materials.

[0028] (3) The boron quantum dot-doped barium titanate of the present invention can change the lattice structure of barium titanate by introducing boron elements, and affect the mechanism of ferroelectric phase transition by forming a solid solution or generating stress at the grain boundary, thereby increasing the Curie temperature of the material; at the same time, the incorporation of boron quantum dots will affect the mobility of the domain wall in barium titanate and increase the domain wall pinning effect, which can also lead to an increase in the Curie temperature;

[0029] (4) The titanium dioxide nanoparticles of the present invention can form a second phase in the aluminum oxide matrix, fill the tiny pores at the grain boundaries, reduce the conductive channels at the grain boundaries, and help reduce the conductivity of the grain boundaries. At the same time, titanium dioxide and aluminum oxide can form a heterostructure, change the microscopic morphology and crystal orientation of the material, optimize the electric domain distribution, reduce the local electric field concentration, and increase the insulation resistance; the nitrogen quantum dots of the modified copper oxide can act as acceptor impurities to introduce additional electrons or holes into the copper oxide, thereby reducing the number of free carriers. In addition, the introduction of nitrogen quantum dots can adjust the band gap width of the copper oxide, making it more difficult for electrons to jump from the valence band to the conduction band, thereby increasing the insulation resistance.

[0030] (5) The mesoporous silica of the present invention can act as a thermal barrier to slow down the speed of heat transfer from the outside to the inside, thereby protecting the internal structure from the influence of high temperature. At the same time, it can act as a flux to help optimize the sintering process so that the ceramic particles can be more closely combined together, thereby obtaining a denser and more uniform microstructure, which is beneficial to improving the accelerated life of MLCC ceramic materials; yttrium-doped zirconium dioxide can inhibit phase change, reduce the volume change caused by phase change, and improve the thermal stability of the material, thereby obtaining a good accelerated life. DETAILED DESCRIPTION

[0031] For the convenience of understanding the present invention, the present invention lists the following embodiments. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.

[0032] The sources of some components in the embodiments and comparative examples are as follows:

[0033] Barium titanate, CAS No. 12047-27-7, purchased from Shanghai MacLean Biochemical Technology Co., Ltd.;

[0034] Alumina I, model PAT-G10A, particle size 100 nm, purchased from Nanjing Baoket New Materials Co., Ltd.;

[0035] Alumina II, model XFI08, particle size 15 nm, purchased from Jiangsu Xianfeng Nanomaterial Technology Co., Ltd.;

[0036] Alumina III, model DCA-10W, particle size 10 μm, purchased from Dongguan Dongchao New Materials Technology Co., Ltd.;

[0037] Cupric oxide, CAS No. 1317-38-0, was purchased from Sinopharm Chemical Reagent Co., Ltd.;

[0038] Silicon dioxide, CAS No. 60676-86-0, was purchased from Shanghai MacLean Biochemical Technology Co., Ltd.;

[0039] Zirconium dioxide, CAS No. 1314-23-4, was purchased from Sinopharm Chemical Reagent Co., Ltd.;

[0040] Boron powder, CAS No. 7440-42-8, was purchased from Shanghai MacLean Biochemical Technology Co., Ltd.;

[0041] Isopropanol, CAS No. 67-63-0, was purchased from Sinopharm Chemical Reagent Co., Ltd.;

[0042] Boric acid, CAS No. 10043-35-3, was purchased from Shanghai MacLean Biochemical Technology Co., Ltd.;

[0043] Hydrogen peroxide, CAS No. 7722-84-1, was purchased from Sinopharm Chemical Reagent Co., Ltd.;

[0044] Sodium borohydride, CAS No. 16940-66-2, was purchased from Sinopharm Chemical Reagent Co., Ltd.;

[0045] Hydrazine hydrate, CAS No. 10217-52-4, was purchased from Sinopharm Chemical Reagent Co., Ltd.;

[0046] Barium hydroxide octahydrate, CAS No. 12230-71-6, was purchased from Sinopharm Chemical Reagent Co., Ltd.;

[0047] Titanium dioxide, CAS No. 13463-67-7, was purchased from Shanghai MacLean Biochemical Technology Co., Ltd.;

[0048] Barium carbonate, CAS No. 513-77-9, was purchased from Shanghai MacLean Biochemical Technology Co., Ltd.;

[0049] Methyltrioctylammonium chloride, CAS No. 63393-96-4, was purchased from Sinopharm Chemical Reagent Co., Ltd.;

[0050] 2-Methyl-2,4-pentanediol, CAS No. 107-41-5, purchased from Sinopharm Chemical Reagent Co., Ltd.;

[0051] Polyethylene glycol, product number P103725, was purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.;

[0052] 2-Azimidazole, CAS No. 56751-68-9, purchased from Tianjin Yankai Technology Co., Ltd.;

[0053] Tetrahydrofuran, CAS No. 109-99-9, was purchased from Sinopharm Chemical Reagent Co., Ltd.;

[0054] Polyethyleneimine, product number E107079, was purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.;

[0055] Ethyl acetate, CAS No. 141-78-6, was purchased from Sinopharm Chemical Reagent Co., Ltd.;

[0056] Copper acetate, CAS No. 6046-93-1, was purchased from Shanghai MacLean Biochemical Technology Co., Ltd.;

[0057] Glacial acetic acid, CAS No. 64-19-7, was purchased from Sinopharm Chemical Reagent Co., Ltd.;

[0058] Sodium hydroxide, CAS No. 1310-73-2, was purchased from Shanghai MacLean Biochemical Technology Co., Ltd.;

[0059] Hexadecyltrimethylammonium chloride, CAS No. 112-02-7, was purchased from Shanghai MacLean Biochemical Technology Co., Ltd.;

[0060] Triethanolamine, CAS No. 102-71-6, was purchased from Shanghai MacLean Biochemical Technology Co., Ltd.;

[0061] Ethyl orthosilicate, CAS No. 78-10-4, was purchased from Sinopharm Chemical Reagent Co., Ltd.;

[0062] Bis-[3-(triethoxysilyl)propyl]-tetrasulfide, CAS No. 40372-72-3, purchased from Sinopharm Chemical Reagent Co., Ltd.;

[0063] Zirconium oxychloride, CAS No. 7699-43-6, purchased from Shanghai MacLean Biochemical Technology Co., Ltd.;

[0064] Yttrium chloride, CAS No. 10025-94-2, was purchased from Sinopharm Chemical Reagent Co., Ltd.;

[0065] Sulfuric acid, CAS No. 7664-93-9, was purchased from Sinopharm Chemical Reagent Co., Ltd.;

[0066] Ammonia water, CAS No. 1336-21-6, was purchased from Sinopharm Chemical Reagent Co., Ltd.

[0067] Example 1

[0068] This embodiment provides a method for preparing a high-insulation, low-temperature sintered MLCC ceramic material, comprising the following steps:

[0069] Preparation of boron quantum dots: In parts by weight, 3 parts of boron powder are added to 80 parts of isopropanol and mixed evenly, then 4 parts of boric acid and 8 parts of hydrogen peroxide are added, and ultrasonic crushing is performed at a power of ~600 W for 2 hours. After the ultrasonic crushing, 4 parts of sodium borohydride are added and stirred for 24 hours. The supernatant is obtained by centrifugation, and 3 parts of hydrazine hydrate are added to the supernatant and ultrasonically shaken for 20 minutes, and freeze-dried to obtain the boron quantum dots.

[0070] Preparation of alumina composite material: In parts by weight, 40 parts of aluminum oxide I (particle size of 100 nm), 20 parts of titanium dioxide, 10 parts of methyl trioctylammonium chloride, 6 parts of 2-methyl-2,4-pentanediol and 2 to 4 parts of polyethylene glycol are mixed evenly and dispersed by ball milling for 30 hours to obtain a mixed slurry; the mixed slurry is heat treated at 800°C for 10 hours, and after cooling to room temperature, it is crushed and ground to obtain the alumina composite material.

[0071] Preparation of modified copper oxide: by weight, 4 parts of 2-imidazole are added to 16 parts of tetrahydrofuran and fully dissolved, and then 6 parts of polyethyleneimine are added, and the reaction is carried out at 70° C. for 20 hours; after the reaction is completed, 3 parts of deionized water are added, and the tetrahydrofuran is dried by a rotary evaporator, and then extracted with ethyl acetate, and the aqueous phase solution is dialyzed for 10 hours, filtered with a filter membrane, and the filtrate is freeze-dried to obtain nitrogen quantum dots; by weight, 40 parts of cupric acetate are added to 160 parts of deionized water and mixed evenly, and then 4 parts of glacial acetic acid and 8 parts of nitrogen quantum dots are added and stirred for 60 minutes, and the temperature is raised to 110° C. and stirred for 20 minutes. After the reaction is completed, 4 parts of sodium hydroxide solution with a molar concentration of 1 mol / L are added, and the precipitate is washed with deionized water and anhydrous ethanol in turn, and dried to obtain the modified copper oxide.

[0072] Preparation of mesoporous silica: In parts by weight, 30 parts of hexadecyltrimethylammonium chloride and 3 parts of triethanolamine are dissolved in 240 parts of deionized water, heated and stirred to 96°C, then 30 parts of ethyl orthosilicate and 20 parts of bis-[3-(triethoxysilyl)propyl]-tetrasulfide are added, stirring is continued for 4 hours, centrifuged, and washed with water to obtain mesoporous silica.

[0073] Preparation of yttrium-doped zirconium dioxide: In parts by weight, 12 parts of zirconium oxychloride, 10 parts of yttrium chloride and 6 parts of polyethylene glycol are added to 120 parts of deionized water and mixed evenly, 20 parts of 25% by mass sulfuric acid solution are added at 80°C to obtain a mixed solution, the mixed solution is heated to 150°C for hydrothermal reaction for 6 hours, cooled to room temperature, ammonia water is added to adjust the pH to 7.8, centrifuged, washed, dried, and calcined to obtain yttrium-doped zirconium dioxide.

[0074] Step S1: In parts by weight, 8 parts of barium hydroxide octahydrate are added to 30 parts of deionized water and stirred for 40 minutes, and then 10 parts of titanium dioxide and 16 parts of deionized water are added, and a hydrothermal reaction is carried out at 104° C. for 4 hours to obtain a hydrothermal product; the hydrothermal product is transferred to a ball mill, 12 parts of barium carbonate and 4 parts of boron quantum dots are added, and the ball mill is carried out for 24 hours, dried, and ground to obtain a powder, and the powder is placed in a muffle furnace for calcination (calcination temperature is 1050° C., heating rate is 6° C. / min, time is 100 minutes), and boron quantum dot-doped barium titanate is obtained;

[0075] Step S2: In parts by weight, 90 parts of boron quantum dot-doped barium titanate, 6 parts of alumina composite material, 5 parts of modified copper oxide, 3 parts of mesoporous silica, 3 parts of yttrium-doped zirconium dioxide and 250 parts of deionized water are mixed and ball-milled for 8 hours to obtain a powder slurry, the powder slurry is spray-granulated and then pressed into a ceramic green body, the ceramic green body is subjected to low-temperature sintering treatment (first heated to 1100°C at a rate of 8°C / min and kept warm for 30 minutes, then cooled to 900°C at a rate of 6°C / min and kept warm for 6 hours) to obtain a high-insulation, low-temperature sintered MLCC ceramic material.

[0076] Example 2

[0077] This embodiment provides a method for preparing a high-insulation, low-temperature sintered MLCC ceramic material, comprising the following steps:

[0078] Preparation of boron quantum dots: In parts by weight, 1 part of boron powder is added to 60 parts of isopropanol and mixed evenly, then 2 parts of boric acid and 6 parts of hydrogen peroxide are added, and ultrasonic crushing is performed at a power of 580 W for 4 hours. After the ultrasonic crushing, 2 parts of sodium borohydride are added and stirred for 20 hours. The supernatant is obtained by centrifugation, 1 part of hydrazine hydrate is added to the supernatant, ultrasonically shaken for 10 minutes, and freeze-dried to obtain the boron quantum dots.

[0079] Preparation of alumina composite material: In parts by weight, 36 parts of aluminum oxide I (particle size of 100 nm), 16 parts of titanium dioxide, 8 parts of methyl trioctylammonium chloride, 4 parts of 2-methyl-2,4-pentanediol and 2 to 4 parts of polyethylene glycol are mixed evenly and dispersed by ball milling for 24 hours to obtain a mixed slurry; the mixed slurry is heat treated at 760°C for 10 hours, and after cooling to room temperature, it is crushed and ground to obtain the alumina composite material.

[0080] Preparation of modified copper oxide: by weight, 2 parts of 2-azidoimidazole are added to 12 parts of tetrahydrofuran and fully dissolved, and then 4 parts of polyethyleneimine are added, and the reaction is carried out at 60° C. for 24 hours; after the reaction is completed, 1 part of deionized water is added, and the tetrahydrofuran is dried by a rotary evaporator, and then extracted with ethyl acetate, and the aqueous phase solution is dialyzed for 8 hours, filtered with a filter membrane, and the filtrate is freeze-dried to obtain nitrogen quantum dots; by weight, 30 parts of cupric acetate are added to 150 parts of deionized water and mixed evenly, and then 2 parts of glacial acetic acid and 4 parts of nitrogen quantum dots are added and stirred for 40 minutes, and the temperature is raised to 100° C. and stirred for 30 minutes. After the reaction is completed, 2 parts of sodium hydroxide solution with a molar concentration of 1 mol / L are added, and the mixture is cooled to room temperature, and the precipitate is washed with deionized water and anhydrous ethanol in turn, and dried to obtain the modified copper oxide.

[0081] Preparation of mesoporous silica: In parts by weight, 20 parts of hexadecyltrimethylammonium chloride and 1 part of triethanolamine are dissolved in 200 parts of deionized water, heated and stirred to 90°C, then 20 parts of ethyl orthosilicate and 10 parts of bis-[3-(triethoxysilyl)propyl]-tetrasulfide are added, stirring is continued for 4 hours, centrifuged, and washed with water to obtain mesoporous silica.

[0082] Preparation of yttrium-doped zirconium dioxide: In parts by weight, 10 parts of zirconium oxychloride, 8 parts of yttrium chloride and 4 parts of polyethylene glycol are added to 100 parts of deionized water and mixed evenly, 16 parts of 25% by mass sulfuric acid solution are added at 70°C to obtain a mixed solution, the mixed solution is heated to 140°C for hydrothermal reaction for 8 hours, cooled to room temperature, ammonia water is added to adjust the pH to 7.4, centrifuged, washed, dried, and calcined to obtain yttrium-doped zirconium dioxide.

[0083] Step S1: In parts by weight, 6 parts of barium hydroxide octahydrate are added to 20 parts of deionized water and stirred for 30 minutes, and then 6 parts of titanium dioxide and 14 parts of deionized water are added, and a hydrothermal reaction is carried out at 100° C. for 6 hours to obtain a hydrothermal product; the hydrothermal product is transferred to a ball mill, 10 parts of barium carbonate and 2 parts of boron quantum dots are added, and ball milling is carried out for 20 hours, drying, and grinding to obtain a powder, and the powder is placed in a muffle furnace for calcination (calcination temperature is 1000° C., heating rate is 4° C. / min, time is 120 minutes), and boron quantum dot-doped barium titanate is obtained;

[0084] Step S2: In parts by weight, 80 parts of boron quantum dots doped barium titanate, 4 parts of alumina composite materials, 3 parts of modified copper oxide, 1 part of mesoporous silica, 1 part of yttrium-doped zirconium dioxide and 200 parts of deionized water are mixed and ball-milled for 6 hours to obtain a powder slurry, the powder slurry is spray granulated and then pressed into a ceramic green body, the ceramic green body is subjected to low-temperature sintering treatment (first heated to 1000°C at a rate of 6°C / min and kept warm for 40 minutes, then cooled to 860°C at a rate of 4°C / min and kept warm for 8 hours) to obtain a high-insulation, low-temperature sintered MLCC ceramic material.

[0085] Example 3

[0086] This embodiment provides a method for preparing a high-insulation, low-temperature sintered MLCC ceramic material, comprising the following steps:

[0087] Preparation of boron quantum dots: In parts by weight, 2 parts of boron powder are added to 70 parts of isopropanol and mixed evenly, then 3 parts of boric acid and 7 parts of hydrogen peroxide are added, and ultrasonic crushing is performed at a power of 590 W for 3 hours. After the ultrasonic crushing, 3 parts of sodium borohydride are added and stirred for 22 hours. The supernatant is obtained by centrifugation, and 2 parts of hydrazine hydrate are added to the supernatant and ultrasonically shaken for 15 minutes, and freeze-dried to obtain the boron quantum dots.

[0088] Preparation of alumina composite material: In parts by weight, 38 parts of aluminum oxide I (particle size of 100 nm), 18 parts of titanium dioxide, 9 parts of methyltrioctylammonium chloride, 5 parts of 2-methyl-2,4-pentanediol and 3 parts of polyethylene glycol are mixed evenly and dispersed by ball milling for 28 hours to obtain a mixed slurry; the mixed slurry is heat treated at 780°C for 11 hours, and after cooling to room temperature, it is crushed and ground to obtain the alumina composite material.

[0089] Preparation of modified copper oxide: by weight, 3 parts of 2-imidazole are added to 14 parts of tetrahydrofuran and fully dissolved, and then 5 parts of polyethyleneimine are added, and the reaction is carried out at 65° C. for 22 hours; after the reaction is completed, 2 parts of deionized water are added, the tetrahydrofuran is dried by a rotary evaporator, and then extracted with ethyl acetate, the aqueous phase solution is dialyzed for 9 hours, filtered with a filter membrane, and the filtrate is freeze-dried to obtain nitrogen quantum dots; by weight, 35 parts of cupric acetate are added to 155 parts of deionized water and mixed evenly, and then 3 parts of glacial acetic acid and 6 parts of nitrogen quantum dots are added and stirred for 50 minutes, the temperature is raised to 105° C. and stirred for reaction for 25 minutes, and after the reaction is completed, 3 parts of sodium hydroxide solution with a molar concentration of 1 mol / L are added, cooled to room temperature, and the precipitate is washed with deionized water and anhydrous ethanol in turn, and dried to obtain the modified copper oxide.

[0090] Preparation of mesoporous silica: In parts by weight, 25 parts of hexadecyltrimethylammonium chloride and 2 parts of triethanolamine are dissolved in 220 parts of deionized water, heated and stirred to 94°C, then 25 parts of ethyl orthosilicate and 15 parts of bis-[3-(triethoxysilyl)propyl]-tetrasulfide are added, stirring is continued for 5 hours, centrifuged, and washed with water to obtain mesoporous silica.

[0091] Preparation of yttrium-doped zirconium dioxide: In parts by weight, 11 parts of zirconium oxychloride, 9 parts of yttrium chloride and 5 parts of polyethylene glycol are added to 110 parts of deionized water and mixed evenly, 18 parts of 25% by mass sulfuric acid solution are added at 75°C to obtain a mixed solution, the mixed solution is heated to 145°C for hydrothermal reaction for 7 hours, cooled to room temperature, ammonia water is added to adjust the pH to 7.6, centrifuged, washed, dried, and calcined to obtain yttrium-doped zirconium dioxide.

[0092] Step S1: In parts by weight, 7 parts of barium hydroxide octahydrate are added to 25 parts of deionized water and stirred for 35 minutes, and then 8 parts of titanium dioxide and 15 parts of deionized water are added, and a hydrothermal reaction is carried out at 102° C. for 5 hours to obtain a hydrothermal product; the hydrothermal product is transferred to a ball mill, 11 parts of barium carbonate and 3 parts of boron quantum dots are added, and ball milling is carried out for 22 hours, drying, and grinding to obtain a powder, and the powder is placed in a muffle furnace for calcination (calcination temperature is 1030° C., heating rate is 5° C. / min, time is 110 minutes), and boron quantum dot-doped barium titanate is obtained;

[0093] Step S2: In parts by weight, 85 parts of boron quantum dot-doped barium titanate, 5 parts of alumina composite material, 4 parts of modified copper oxide, 2 parts of mesoporous silica, 2 parts of yttrium-doped zirconium dioxide and 220 parts of deionized water are mixed and ball-milled for 7 hours to obtain a powder slurry, the powder slurry is spray-granulated and then pressed into a ceramic green body, the ceramic green body is subjected to low-temperature sintering treatment (first heated to 1050°C at a rate of 7°C / min and kept warm for 35 minutes, then cooled to 880°C at a rate of 5°C / min and kept warm for 7 hours) to obtain a high-insulation, low-temperature sintered MLCC ceramic material.

[0094] Comparative Example 1

[0095] This comparative example provides a method for preparing an MLCC ceramic material, which differs from Example 1 in that commercially available barium titanate is used instead of boron quantum dots to dope barium titanate.

[0096] Comparative Example 2

[0097] This comparative example provides a method for preparing an MLCC ceramic material, which differs from Example 1 in that aluminum oxide I is used instead of the aluminum oxide composite material.

[0098] Comparative Example 3

[0099] This comparative example provides a method for preparing an MLCC ceramic material, which differs from Example 1 in that aluminum oxide II is used instead of aluminum oxide I to prepare an aluminum oxide composite material.

[0100] Comparative Example 4

[0101] This comparative example provides a method for preparing an MLCC ceramic material, which differs from Example 1 in that aluminum oxide III is used instead of aluminum oxide I to prepare an aluminum oxide composite material.

[0102] Comparative Example 5

[0103] This comparative example provides a method for preparing an MLCC ceramic material, which differs from Example 1 in that commercially available copper oxide is used instead of modified copper oxide.

[0104] Comparative Example 6

[0105] This comparative example provides a method for preparing an MLCC ceramic material, which differs from Example 1 in that commercially available silica is used instead of mesoporous silica.

[0106] Comparative Example 7

[0107] This comparative example provides a method for preparing an MLCC ceramic material, which differs from Example 1 in that commercially available zirconium dioxide is used instead of yttrium-doped zirconium dioxide.

[0108] The performance of the MLCC ceramic materials provided in the above embodiments and comparative examples was tested, and the testing method was as follows:

[0109] (1) Curie temperature test: A differential scanning calorimeter (model DSC25, TA Instrument, USA) was used to measure the Curie temperature of MLCC ceramic materials. The samples were placed in a nitrogen atmosphere with a heating and cooling rate of 10°C / min. The positions of the endothermic and exothermic peaks were observed, and their average value was taken as the Curie temperature of the material.

[0110] (2) Insulation resistance test: The MLCC ceramic material was tested using an insulation resistance tester (model TH2681, Changzhou Tonghui Electronics). A voltage of 4 kV / mm was applied at 25°C to measure the insulation resistance of the multilayer ceramic capacitor and take the average value.

[0111] (3) Accelerated life test: The MLCC ceramic material is subjected to an accelerated life test using a highly accelerated life test chamber (model PC422R8, HIRAYAMA, Japan). A pressure test is performed at 150°C and 10V / μm. The time when the MLCC ceramic material fails is recorded and the average value of the failure time is taken as the average value of the accelerated life of the MLCC ceramic material.

[0112] The above performance test data is shown in Table 1.

[0113] Table 1 Performance test results

[0114] Curie temperature (℃) Insulation resistance(MΩ) Accelerated life span (min) Example 1 148.7 613 318 Example 2 148.1 604 309 Example 3 148.4 609 314 Comparative Example 1 139.8 376 195 Comparative Example 2 140.3 381 198 Comparative Example 3 144.7 492 246 Comparative Example 4 144.1 485 239 Comparative Example 5 142.7 393 211 Comparative Example 6 141.5 389 207 Comparative Example 7 140.9 384 202

[0115] From the above content, it can be seen that the present invention prepares high-insulation, low-temperature sintered MLCC ceramic materials (Examples 1 to 3) by doping the main material barium titanate with boron quantum dots and using alumina composite materials, modified copper oxide, mesoporous silica and yttrium-doped zirconium dioxide together. The Curie temperature is 148.1 to 148.7°C, the insulation resistance is 604 to 613 MΩ, and the accelerated life is 309 to 318 min.

[0116] Compared with Example 1, commercially available barium titanate was used instead of boron quantum dot doped barium titanate, the Curie temperature was lowered, the insulation resistance was reduced, and the accelerated life was worse (Comparative Example 1); Compared with Example 1, aluminum oxide I was used to replace the aluminum oxide composite material, the Curie temperature was lowered, the insulation resistance was reduced, and the accelerated life was worse (Comparative Example 2); Compared with Example 1, aluminum oxide II was used to replace aluminum oxide I for the preparation of the aluminum oxide composite material. Since the particle size of aluminum oxide II was too small, the modification effect was not good, the Curie temperature was lowered, the insulation resistance was reduced, and the accelerated life was worse (Comparative Example 3); Compared with Example 1, aluminum oxide III was used to replace aluminum oxide I for aluminum oxide Preparation of composite materials. Since the particle size of aluminum oxide III is too large and the modification effect is not good, the Curie temperature is reduced, the insulation resistance is reduced, and the accelerated life is deteriorated (Comparative Example 4); compared with Example 1, commercially available copper oxide is used instead of modified copper oxide, the Curie temperature is reduced, the insulation resistance is reduced, and the accelerated life is deteriorated (Comparative Example 5); compared with Example 1, commercially available silicon dioxide is used instead of mesoporous silicon dioxide, the Curie temperature is reduced, the insulation resistance is reduced, and the accelerated life is deteriorated (Comparative Example 6); compared with Example 1, commercially available zirconium dioxide is used instead of yttrium-doped zirconium dioxide, the Curie temperature is reduced, the insulation resistance is reduced, and the accelerated life is deteriorated (Comparative Example 7).

[0117] In summary, the present invention dopes the main material barium titanate with boron quantum dots, which can combine with the nitrogen quantum dots in the modified copper oxide during the subsequent sintering process to form a reinforcement phase in the ceramic material. At the same time, the introduced mesoporous silica can provide a place for the combination of boron quantum dots and nitrogen quantum dots, and can also be used as a carrier to load titanium dioxide nanoparticles in the alumina composite material and rare earth elements in yttrium-doped zirconium dioxide. The mesoporous silica is used as a bridge to form a high-density composite structure, which improves the Curie temperature and insulation resistance of the MLCC ceramic material through synergistic effects, while ensuring a good accelerated life.

Claims

1. A method for preparing a high-insulation, low-temperature sintered MLCC ceramic material, characterized in that: The following steps are involved: Step S1: by weight, 6 to 8 parts of barium hydroxide octahydrate are added to 20 to 30 parts of deionized water, and stirred for 30 to 40 minutes, and then 6 to 10 parts of titanium dioxide and 14 to 16 parts of deionized water are added, and a hydrothermal reaction is carried out at 100 to 104° C. for 4 to 6 hours to obtain a hydrothermal product; the hydrothermal product is transferred to a ball mill, 10 to 12 parts of barium carbonate and 2 to 4 parts of boron quantum dots are added, and the ball milling is carried out for 20 to 24 hours, dried, and ground to obtain a powder, and the powder is placed in a muffle furnace for calcination to obtain boron quantum dot-doped barium titanate; Step S2: In parts by weight, 80 to 90 parts of boron quantum dots doped with barium titanate, 4 to 6 parts of aluminum oxide, 3 to 5 parts of copper oxide, 1 to 3 parts of silicon dioxide, 1 to 3 parts of zirconium dioxide and 200 to 250 parts of deionized water are mixed and ball-milled for 6 to 8 hours to obtain a powder slurry, the powder slurry is spray-granulated and then pressed into a ceramic body, the ceramic body is subjected to low-temperature sintering treatment to obtain a high-insulation, low-temperature sintered MLCC ceramic material.

2. The method for preparing a high-insulation, low-temperature sintered MLCC ceramic material according to claim 1, characterized in that: The calcination treatment conditions include: calcination temperature of 1000-1050° C., heating rate of 4-6° C. / min, and time of 100-120 min.

3. The method for preparing a high-insulation, low-temperature sintered MLCC ceramic material according to claim 1, characterized in that: The preparation method of the boron quantum dots comprises: adding 1 to 3 parts of boron powder to 60 to 80 parts of isopropanol by weight and mixing evenly, then adding 2 to 4 parts of boric acid and 6 to 8 parts of hydrogen peroxide, ultrasonically crushing for 2 to 4 hours at a power of 580 to 600 W, adding 2 to 4 parts of sodium borohydride after the ultrasonic crushing, stirring for 20 to 24 hours, centrifuging to obtain a supernatant, adding 1 to 3 parts of hydrazine hydrate to the supernatant, ultrasonically shaking for 10 to 20 minutes, and freeze-drying to obtain the boron quantum dots.

4. The method for preparing a high-insulation, low-temperature sintered MLCC ceramic material according to claim 1, characterized in that: The aluminum oxide is an aluminum oxide composite material; The preparation method of the aluminum oxide composite material comprises: mixing 36 to 40 parts of aluminum oxide, 16 to 20 parts of titanium dioxide, 8 to 10 parts of methyl trioctyl ammonium chloride, 4 to 6 parts of 2-methyl-2,4-pentanediol and 2 to 4 parts of polyethylene glycol in parts by weight, and then ball milling and dispersing them for 24 to 30 hours to obtain a mixed slurry; heat treating the mixed slurry at 760 to 800° C. for 10 to 12 hours, and crushing and grinding the mixed slurry after cooling to room temperature to obtain the aluminum oxide composite material.

5. The method for preparing a high-insulation, low-temperature sintered MLCC ceramic material according to claim 4, characterized in that: The particle size of the aluminum oxide is 100 to 300 nm.

6. The method for preparing a high-insulation, low-temperature sintered MLCC ceramic material according to claim 1, characterized in that: The copper oxide is modified copper oxide; The preparation method of the modified copper oxide comprises: adding 2-4 parts of 2-azidoimidazole to 12-16 parts of tetrahydrofuran by weight and fully dissolving them, then adding 4-6 parts of polyethyleneimine, and reacting them at 60-70° C. for 20-24 hours; after the reaction is completed, adding 1-3 parts of deionized water, using a rotary evaporator to spin dry the tetrahydrofuran, then extracting with ethyl acetate, dialyzing the aqueous phase solution for 8-10 hours, filtering with a filter membrane, and freeze-drying the filtrate to obtain nitrogen quantum dots; adding 30-40 parts of copper acetate to 150-160 parts of deionized water by weight and mixing them evenly, then adding 2-4 parts of glacial acetic acid and 4-8 parts of nitrogen quantum dots and stirring for 40-60 minutes, heating to 100-110° C. and stirring and reacting for 20-30 minutes, adding 2-4 parts of sodium hydroxide solution with a molar concentration of 1 mol / L after the reaction is completed, cooling to room temperature, washing the precipitate with deionized water and anhydrous ethanol in turn, and drying to obtain the modified copper oxide.

7. The method for preparing a high-insulation, low-temperature sintered MLCC ceramic material according to claim 1, characterized in that: The silicon dioxide is mesoporous silicon dioxide; The preparation method of the mesoporous silica comprises: dissolving 20 to 30 parts of hexadecyltrimethylammonium chloride and 1 to 3 parts of triethanolamine in 200 to 240 parts of deionized water by weight, heating and stirring to 90 to 96° C., then adding 20 to 30 parts of ethyl orthosilicate and 10 to 20 parts of bis-[3-(triethoxysilyl)propyl]-tetrasulfide, continuing stirring for 4 to 6 hours, centrifuging, and washing with water to obtain the mesoporous silica.

8. The method for preparing a high-insulation, low-temperature sintered MLCC ceramic material according to claim 1, characterized in that: The zirconium dioxide is yttrium-doped zirconium dioxide; The preparation method of yttrium-doped zirconium dioxide comprises: adding 10 to 12 parts of zirconium oxychloride, 8 to 10 parts of yttrium chloride and 4 to 6 parts of polyethylene glycol to 100 to 120 parts of deionized water by weight and mixing them evenly, adding 16 to 20 parts of 25% by mass sulfuric acid solution at 70 to 80° C. to obtain a mixed solution, heating the mixed solution to 140 to 150° C. for hydrothermal reaction for 6 to 8 hours, cooling to room temperature, adding ammonia water to adjust the pH to 7.4 to 7.8, centrifuging, washing, drying and calcining to obtain yttrium-doped zirconium dioxide.

9. The method for preparing a high-insulation, low-temperature sintered MLCC ceramic material according to claim 1, characterized in that: The conditions of the low temperature sintering treatment include: firstly heating to 1000-1100°C at a rate of 6-8°C / min and keeping the temperature for 30-40min, then cooling to 860-900°C at a rate of 4-6°C / min and keeping the temperature for 6-8h.

10. High insulation low temperature sintered MLCC ceramic material, characterized in that: Prepared according to the method according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • MLCC ceramic dielectric materials and their preparation methods, high-temperature stable MLCC ceramics and their preparation methods, applications

    CN114956808B

  • Preparation method of adjustable fluorescent nitrogen dots

    CN109097025A

  • Nano barium titanate microcrystal and preparation method thereof, and barium titanate powder and preparation method thereof

    CN110092657A

  • Preparation method and applications of boron quantum dots

    CN110194464A

  • Iron-blocking magnetic nano-drug responding to tumor microenvironment, preparation method and application

    CN113350524A